Development and characterisation of caesium lead halide perovskite nanocomposite scintillators for X-ray detection - O’Neill, Joseph; Braddock, Isabel; Crean, Carol; Ghosh, Joydip; Masteghin, Mateus; Richards, Sion; Wilson, Matthew; Sellin, Paul (Frontiers in Physics, 2023)
We present work on the development of mixed-halide perovskite (CsPbCl(x)Br(1-x) nanocrystal scintillators for X-ray detection applications. The effect of the varying the halide composition on the resulting peak emission and light yield is discussed, with the CsPbBr3 materials displaying the greatest light yield. These perovskite nanocrystals were successfully loaded into PMMA, an inert plastic, at 2% mass weighting and the responses of these composites were compared to that of their colloidal dispersions. The composites were also characterised in terms of the radioluminescent light yield and decay response, alongside their X-ray sensitivity, in which the PMMA-CsPbBr3 composites again outperformed the materials containing Cl- anions.